Vivienne Binns - on and through the surface - Jaspers, Anneke; Matthews, Hannah (Monash University Museum of Art, 2022)
Published to accompany and exhibition held at Monash University Museum of Art, Melbourne, 05 February-14 April, 2022 and the Museum of Contemporary Art Australia, Sydney, 15 July-25 September, 2022. Includes fully illustrated plate and list of works sections, five commissioned essays, one interview, historical writings by the artist and a detailed biography and bibliography.
Impressum: First published on the occasion of the exhibition "Vivienne Binns: On and through the Surface", Monash University Museum of Art, Melbourne, 5 February - 14 April 2022, Museum of Contemporary Art Australia, Sydney, 15 July - 25 September 2022
First edition of 1000
Keywords: Binns, Vivienne -- 1940-; Ausstellungskatalog -- Monash University Museum of Art -- 05.02.2022-14.04.2022 -- Caulfield, Victoria; Ausstellungskatalog -- Museum of Contemporary Art -- 15.07.2022-25.09.2022 -- Sydney; Bildband